Samaun Bakri: Nationalist Portrait in 1925-1948 - Abdul Salam (Yupa: Historical Studies Journal, 2018)
Samaun Bakri is one of many figures from Nagari Kurai Taji Pariaman West Sumatra, which enliven the national political stage. His movement in the Dutch Colonial period, began when he attended in Sumatra Thawalib Padang Panjang. The Kuminih movement, fronted by Communist propagandists, has changed its paradigm of thinking from moderate to radical. Sometimes Samaun is often the target of arrest with allegations of infidelity. This paper is compiled based on historical method, consist of; heuristics, criticism, interpretation, and historiography. The world of Islamic movement and modernization has indeed influenced the way of Samaun thinking. Several times, he was involved in the press, ranging from Persamaan, Sasaran, Penabur, and often wrote harsh criticisms of the Dutch government. After the Silungkang incident, he crossed over to the Partai Nasional Indonesia (PNI). During the Japanese occupation, he was involved in the management of PUTERA and Jawa Hokokai. His political career post-independence immediately dashed, when he served as Deputy Governor of West Java in 1946, KNIP members represent West Java, and became Deputy Resident of Banten in 1946-1948.